ANALISIS KENDALA PENERAPAN MODEL PEMBELARAN INKUIRI PADA MATA PELAJAR MATEMATIKA DI TINGKAT SEKOLAH DASAR - Andi Muhadi; Encep Supriatna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the challenges faced by teachers and students in implementing the inquiry-based learning model at the elementary school level. A qualitative approach was employed, utilizing direct observation, document analysis such as lesson plans, and field notes. The research was conducted in a single elementary school classroom at SDN Panjangjaya 1 to limit the scope of the study. The research focus encompassed both students and teachers, considering the latter as facilitators. The findings reveal that the main challenges for teachers include limited time for preparation and implementation of the inquiry method, as well as difficulties in designing relevant questions that stimulate students' curiosity. For students, the primary challenges consist of limited critical thinking skills, difficulty understanding complex problems, and low motivation for independent learning. This study concludes that implementing inquiry-based learning in mathematics at the elementary level requires additional support, such as teacher training and method adaptation according to students' proficiency levels. The findings provide valuable insights into the implementation of inquiry-based learning in elementary schools